1990
DOI: 10.1002/jez.1402550107
|View full text |Cite
|
Sign up to set email alerts
|

Lampbrush and mitotic chromosomes of the hemiclonally reproducing hybrid Rana esculenta and its parental species

Abstract: Mitotic chromosomes of the European water frogs Rana ridibunda and Rana lessonae, the parental species of Rana esculenta, differ significantly in their centromeric regions: when C-banded or when made fluorescent, the centromeres of R. ridibunda (and of ridibunda chromosomes in R. esculenta) are visible as a conspicuous dark granule or as a conspicuous fluorescent spot; the centromeres of R. lessonae (and of the lessonae chromosomes in R. esculenta) are inconspicuous or not fluorescent. Lampbrush chromosomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 33 publications
2
65
0
Order By: Relevance
“…Like other non-hybridogenetic hybrids between Rana ridibunda and Rana lessonae (Hotz et al, 1985;Bucci et al, 1990), it evidenced a disturbed gametogenesis caused by the combination of the two heterospecific genomes. The observed approximately triploid spermatogonial metaphases, for example, probably reflect endoreduplication of the L genome without prior elimination of the R genome.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Like other non-hybridogenetic hybrids between Rana ridibunda and Rana lessonae (Hotz et al, 1985;Bucci et al, 1990), it evidenced a disturbed gametogenesis caused by the combination of the two heterospecific genomes. The observed approximately triploid spermatogonial metaphases, for example, probably reflect endoreduplication of the L genome without prior elimination of the R genome.…”
Section: Discussionmentioning
confidence: 77%
“…Hybrids between Rana ridibunda and Rana lessonae, for example, are sterile when the R genome stems from southern parts of the Rana ridibunda range (Hotz et al, 1985 ;Berger et al, 1994 b;unpublished data). Such non-hybridogenetic hybrids show incomplete pairings between the Rana ridibunda and Rana lessonae genomes in meiosis I, which probably lead to aneuploid gametes and thus render the individuals sterile (Hotz et al, 1985;Bucci et al, 1990). The non-hybridogenetic offspring of cross 02.43 is an example of such hybrids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the germ cells in green frogs of the genus Rana has been thoroughly investigated by means of cytological, genetic and cytogenetic approaches (Uzzell et al 1980;Bucci et al 1990Bucci et al , 1999Ragghianti et al 1995;Ogielska & Kotusz 2004). Interesting information emerged from studies about Rana esculenta gametogenesis (Chieffi et al 2000;Ferrara et al 2004;Meccariello et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid condition is recovered at the next generation by backcrossing with the parental species whose genome was eliminated (Tunner & Heppich-Tunner 1991). In spite of the molecular mechanisms of hybridogenesis is still unknown, cytogenetic studies and morphological inspections demonstrated the presence of alterations in the gametogenesis of the hybridogenetic frogs (Bucci et al 1990;Ogielska 1990). In addition, a delay in sexual maturation was observed in R. esculenta when compared to the parental species .…”
Section: Introductionmentioning
confidence: 99%